Baby MIND: a magnetized segmented neutrino detector for the WAGASCI experiment. (19th July 2017) - Antonova, M.; Asfandiyarov, R.; Bayes, R.; Benoit, P.; Blondel, A.; Bogomilov, M.; Bross, A.; Cadoux, F.; Cervera, A.; Chikuma, N.; Dudarev, A.; Ekelöf, T.; et al.
Abstract: T2K (Tokai-to-Kamioka) is a long-baseline neutrino experiment in Japan designed to study various parameters of neutrino oscillations. A near detector complex (ND280) is located 280 m downstream of the production target and measures neutrino beam parameters before any oscillations occur. ND280's measurements are used to predict the number and spectra of neutrinos in the Super-Kamiokande detector at the distance of 295 km. The difference in the target material between the far (water) and near (scintillator, hydrocarbon) detectors leads to the main non-cancelling systematic uncertainty for the oscillation analysis. In order to reduce this uncertainty a new WAter-Grid-And-SCintillator detector (WAGASCI) has been developed. A magnetized iron neutrino detector (Baby MIND) will be used to measure momentum and charge identification of the outgoing muons from charged current interactions. The Baby MIND modules are composed of magnetized iron plates and long plastic scintillator bars read out at the both ends with wavelength shifting fibers and silicon photomultipliers. The front-end electronics board has been developed to perform the readout and digitization of the signals from the scintillator bars. Detector elements were tested with cosmic rays and in the PS beam at CERN. The obtained results are presented in this paper.